Fertilizer doses and mulching effect to mitigate soil salinity and maximize yield of watermelon (Citrullus lanatus L.) in coastal region of Bangladesh - Md. Mainul Islam; Md. Mahmudul Hasan Khan; Md. Shahidul Islam Khan; Gazi Nazmul Hasan; Nasira Akter; Krisna Chandra Saha; Md. Torikul Islam; Md. Rashidul Hasan Anik (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
An experiment was conducted in the rabi season at Patuakhali, Bangladesh to verify the effect of different mulching materials for watermelon production under farmers field condition. The aim of this research was to test the possibility of salinity damage can be reduced by elevating potassium (K) fertilization rate on watermelon yield and nutrient uptake under salt stress condition. Four different fertilizer doses T1 = Soil Test Based (STB), T2 = STB + 50% K, T3 = Integrated Plant Nutrients System (IPNS) approach with 5 tonha-1 cowdung (CD) + 50% K and T4 = Farmers practices with many materials usedP1 = Silver color polythene mulch, P2 = Straw mulch, P3 = No mulch combination. Twenty days old seedling were used in farmers' field. Other nutrients were also applied following STB method. Fertilizer used as the rates of N117P30K30S25 (T1), N117P30K37S25 (T2), N92P22.5K45S25 with 5 tonha-1cowdung (T3) and N100P40K35S30 (T4). All the plant growth, yield and quality characters were superior in T3 with silver polythene (31.96 tonha-1) while plants without mulch and STB method resulted poor growth and yield of 24.31 tonha-1. The higher rates of K contributed to 7- 27% increased yield over only STB dose for Patuakhali which implies the necessity of higher dose of K in salt affected soil in strengthening yield. With economic point of view, T3 (IPNS with 5 ton/ha cowdung + 50% K and silver polythene mulch) seedling reported the highest net return of 375780 Bd TK and found more economical with highest cost benefit ratio.